Jordanian editorial cartoons: A multimodal approach to the cartoons of Emad Hajjaj. (September 2016) - Al-Masri, Hanada
Abstract: This paper investigates Jordanian editorial cartoons drawn by the eminent Jordanian cartoonist Emad Hajjaj. It aims at analyzing Hajjaj's cartoons within a multimodal approach to context with a consideration of three types of sub-contexts essential to the understanding of the cartoon's message: (1) macro-context, (2) microcontext and (3) dynamic context. The data is based on a corpus of 300 cartoons analyzed within a general linguistic framework inspired by Van Dijk's (2008) theory of context models. Two main results emerge: First, Hajjaj's cartoons take into full consideration the verbal, visual, and socio-cultural modes to create visually stimulating images and socioculturally relevant issues. Second, the study presents an inventory of Hajjaj's lexical devices and innovative techniques. Highlights: A multimodal approach to context is essential to the decoding and appreciating of Hajjaj's editorial cartoons. The study provides fresh insights into how verbal, visual, and socio-cultural modes contribute to the message of the cartoon. Hajjaj's cartoons challenge readers through an implicit political criticism embedded within the broader framework of social criticism. The study yields an inventory of linguistic characteristics and stylistic techniques such as word play, pun, and spoonerism. The results of this study help explain the uniqueness and popularity of Hajjaj's cartoons.